Sol-gel synthesis of new TiO2/activated carbon photocatalyst and its application for degradation of tetracycline. Issue 5 (1st April 2017) - Martins, Alessandro C.; Cazetta, André L.; Pezoti, Osvaldo; Souza, João R.B.; Zhang, Tao; Pilau, Eduardo J.; Asefa, Tewodros; Almeida, Vitor C.
Abstract: A new efficient photocatalyst consisting of TiO2 -activated carbon composite (TiO2 /AC) was synthesized by sol-gel process and applied to decomposition of tetracycline (TC). Its properties and catalytic activity were evaluated in comparison with bare TiO2 and P25, based on several characterization techniques and TC photodegradation kinetic studies. The results showed TiO2 /AC has better structural and electronic features for photocatalysis; SBET of 129 m 2 g –1, exclusively anatase phase, crystal size of 8.53 nm and band gap energy of 3.04 eV. The catalytic activity of the material was evaluated based on photodegradation kinetic studies of TC from aqueous solution (with initial concentration=50 mg L −1 and catalyst dosage=1.0 g L −1 ). Non-linear kinetic model of pseudo-first order were fitted to the resulting experimental data. The apparent first-order rate constant ( k app =42.9×10 –3 min –1 ) and half-life time ( t 1/2 =16.1 min) determined for TiO2 /AC were better than those for P25 and bare TiO2 . TC degradation by-products were investigated by HPLC-MS, showing TC was completely degraded after 75 min, producing fragments with m/z smaller than 150. Graphical abstract: